2019
DOI: 10.1097/md.0000000000014657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-acting loop diuretic doses and cardiac sympathetic nerve abnormalities on outcomes of patients with reduced left ventricular function

Abstract: Recent studies reported that high doses of short-acting loop diuretics are associated with poor outcomes in patients with heart failure (HF). Short-acting loop diuretics have been shown to activate the renin-angiotensin system (RAS) and have no favorable effects on cardiac sympathetic nervous system (SNS) activity. The goal of this study is to investigate the relationship between daily doses of furosemide and the outcomes of patients with left ventricular dysfunction (LVD) from the viewpoint of cardiac SNS abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Research conducted by Tyler P. Rasmussen et al and Hisamitsu Onitsuka et al also demonstrated that renal function worsened in furosemide-treated patients. 16,19 In the study of Tyler P. Rasmussen et al it was found that furosemide cause AKI, and in this study female patients suffered from AKI more than men (p = 0.0081). 19 Based on the results of the study of Hisamitsu Onitsuka et al, patients treated with furosemide 40mg per day, had low serum sodium (P<0.0001) and eGFR (P=0.011).…”
Section: Jkd Volume 11 Nomor 4 Juli 2022mentioning
confidence: 46%
See 2 more Smart Citations
“…Research conducted by Tyler P. Rasmussen et al and Hisamitsu Onitsuka et al also demonstrated that renal function worsened in furosemide-treated patients. 16,19 In the study of Tyler P. Rasmussen et al it was found that furosemide cause AKI, and in this study female patients suffered from AKI more than men (p = 0.0081). 19 Based on the results of the study of Hisamitsu Onitsuka et al, patients treated with furosemide 40mg per day, had low serum sodium (P<0.0001) and eGFR (P=0.011).…”
Section: Jkd Volume 11 Nomor 4 Juli 2022mentioning
confidence: 46%
“…Based on the results of data synthesis, it was found that the side effects of furosemide therapy in the treatment of heart failure patients were in the form of electrolyte disturbances, such as 11,12,13,14,15,16 : hyponatremia 11,14 ; hypokalemia 12,14,17 ; dan hypomagnesemia 12 , heart rhythm disturbances 12,15 , worsening of kidney function and worsening of AKI 11,12,13,18,16,19 , which were characterized by an increase in BUN; creatinine; and decreased GFR; hypotension 20 , an increase in plasma renin 11 , as well as an increased risk of bone fragility that can lead to fracture. 21,22 The incidence of hypochloremia, hypocalcemia, and dehydration in the study hypothesis, was not identified by the reviewed journals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher doses of loop diuretics have been shown to activate the renin‐angiotensin system. 15 , 16 Further, angiotensin II signalling augments the expression of Ang‐2, a proangiogenic signal, which activates angiogenesis in the presence of vascular endothelial growth factor. 17 Finally, an arteriovenous malformation caused by angiogenesis can cause GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that activation of the RAS and hyperosmolarity may lead to overexpression of URAT1 [ 141 ]. A similar scenario can be envisioned for loop diuretics, since they also activate the RAS [ 142 , 143 ]. Although the overexpression of URAT1 upon treatment with diuretics has not been documented in public databases, upregulation of the sodium–hydrogen exchanger NHE3 upon increased angiotensin II has been reported [ 144 ].…”
Section: Drug-induced Hyperuricemiamentioning
confidence: 99%